1989
DOI: 10.1152/ajpheart.1989.257.6.h1773
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of a transient outward current to repolarization in human atrium

Abstract: Conventional microelectrode recordings combined with enzymatic cell dispersion methods and a single microelectrode voltage-clamp technique were used to record transmembrane action potentials and ionic currents in isolated single myocytes and in excised segments of human right atrium. Recordings of the outward current(s), which is responsible for the resting potential and early repolarization of the action potential in human right atrium, consistently showed that this tissue has 1) a relatively small inwardly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 0 publications
10
63
1
Order By: Relevance
“…Nevertheless, previous studies have indicated that I TO may influence late repolarisation indirectly, through secondary effects on additional ion currents, such as the L-type Ca 2+ current, I CaL , 22 and K + currents. 23 In the present study, there is evidence that slow reactivation of I TO1 was responsible for the marked shortening of APD 50 observed at low rates in atrial cells but not in AV nodal cells. However, I TO was not involved in the rate response of either late repolarisation or refractoriness at low or high rates in either cell type.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Nevertheless, previous studies have indicated that I TO may influence late repolarisation indirectly, through secondary effects on additional ion currents, such as the L-type Ca 2+ current, I CaL , 22 and K + currents. 23 In the present study, there is evidence that slow reactivation of I TO1 was responsible for the marked shortening of APD 50 observed at low rates in atrial cells but not in AV nodal cells. However, I TO was not involved in the rate response of either late repolarisation or refractoriness at low or high rates in either cell type.…”
Section: Discussionsupporting
confidence: 46%
“…Moreover, in the rabbit, the contribution of I TO to the APD rate-relation in the AV node might be expected to be less than in the atrium, due to the relatively small I TO in mid-nodal cells. 11,21 Additionally, ionic mechanisms which may influence late repolarisation secondarily to I TO modulation, 22,23 might be expected to influence the ERP. An investigation into the contribution of I TO to the rate relation of either the APD or the ERP has not yet been carried out in AV nodal cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was demonstrated that I'o is present in human atrial cells and plays a role in the repolarization of the action potential (Escande et al, 1987;Shibata et al, 1989). In terms of IKI, it has been recently reported that IK, is mainly responsible for final repolarization in rabbit ventricular cells (Shimoni et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological blockade of I to with 4-AP causes an increase in action potential amplitude and duration (34) and increases force generation (94). The distribution of I to within the myocardium is nonuniform and contributes toward regional variations in action potential waveforms (6, 15, 121).…”
Section: A-type Currents In Non-smooth Muscle Tissuesmentioning
confidence: 99%